Assessment of emotion word vocabulary and its contribution to reading comprehension. (5th January 2023) - Sabag-Shushan, Tami; Katzir, Tami; Prior, Anat
Abstract: The contribution of vocabulary to academic achievements in general and to reading comprehension (RC) in particular has led to the development of various tools for vocabulary assessment. However, existing assessments do not distinguish between word types, and specifically, they do not target emotion vocabulary, despite growing recognition of the importance of emotional processing to RC ability. In this study, we first describe the development of a novel vocabulary assessment in Hebrew – Herut – and examine its validity and sensitivity. This assessment includes both emotion words and nonemotion words, and is based on curriculum. Next, we studied the contribution of the emotion and nonemotion words subscales of the Herut to RC in a sample of 1, 333 Hebrew-speaking fourth- and fifth-grade students. Both types of vocabulary knowledge made significant independent contributions to RC, and the contribution of emotion words was slightly larger than that of nonemotion words. Finally, the Herut measure was found to be more predictive of RC than a general vocabulary measure in Hebrew.